The Use of Padlet in Writing Learning Reflection: Students’ Perspectives - Kurniati, Fadhika; Dzulfikri, Dzulfikri; Bandono, Adi (Universitas Trunojoyo Madura, 2025)
Digital learning media is indeed developing and plays an important role in creating a pleasant learning environment that can accommodate students' learning needs. Padlet provides space for students to learn digitally, especially through the activity of writing learning reflections. This research is aimed at finding out students' perspectives on the use of Padlet media to write reflection activities. This study was attended by 50 students in the seventh grade using a qualitative research method in the form of phenomenology design. Data was obtained from questionnaires distributed via Google Form, observations, and interviews. The data obtained from the Google Form is strengthened by conducting interviews, where the purpose of the interviews is to check the consistency of the Google Form results. The finding revealed that students gave positive responses regarding Padlet media. They perceived that Padlet media was easy to use, helped the students to discuss developing ideas and exchange ideas, eliminated boredom, increased the students’ participation in writing reflections, and increased students’ learning motivation. It is concluded that Padlet can serve as an effective digital tool to support reflective learning. Future studies are suggested to investigate Padlet's effectiveness in comparison with other digital platforms or in different educational contexts.